The Utilization of Brantas River in the era of Kediri until Majapahit Kingdom - Mawardi Purbo Sanjoyo (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2021)
Basically, this study aims to describe the historical picture following the research focuses that have been raised. The purpose of this study is to determine and describe the historical function of the Brantas river during the Kadiri kingdom to Majapahit. The author uses the historical research method as the method. In this study, the author describes and interprets the relationship or a current condition, processes, opinions, and impacts. The steps taken in the historical research method include heuristics, source criticism, interpretation, and historiography. The history of the Brantas River has long been enshrined in various kinds of inscriptions, including the Harinjing Inscription, the Kamalagyan Inscription, and the Canggu Inscription. Based on the identification of historical sources, the Brantas River has a strategic position because of the principle of usefulness for human life in the past. Since the era of the Kediri Kingdom, the Brantas River has been used as a source of water for agriculture and trade. This can be found in the writings on the Kamalagyan inscription. Utilization was continued until the era of the Majapahit kingdom. Hayam Wuruk (1350-1389 AD) specially treated the Brantas River by publishing the Canggu inscription in which it contained an increase in the status of port villages along the Brantas and Bengawan Solo rivers to become autonomous regions.